2020
DOI: 10.1007/s11033-020-05691-1
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of T cell receptor signaling by protein acyltransferase DHHC21

Abstract: S-acylationreversible post-translational lipidation of cysteine residuesis emerging as an important regulatory mechanism in T cell signaling. Dynamic S-acylation is critical for protein recruitment into the T cell receptor complex and initiation of the subsequent signaling cascade. However, the enzymatic control of protein S-acylation in T cells remains poorly understood. Here, we report a previously uncharacterized role of DHHC21, a member of the mammalian family of DHHC protein acyltransferases, in regulatio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 38 publications
(45 reference statements)
2
23
0
Order By: Relevance
“…We next sought to examine the effect of the ΔF233 mutation on the acyltransferase activity of DHHC21. Previously, we detected direct stimulus-dependent interaction between DHHC21 and the Src-family kinase Lck (Fan et al, 2020). Furthermore, we showed that shRNAmediated downregulation of DHHC21 significantly decreased Sacylation of Lck and PLC-γ1 in resting EL4 lymphoma cells, suggesting that these proteins are direct targets of DHHC21 (Fan et al, 2020).…”
Section: Dhhc21 Mediates Tcr-induced S-acylation Of T Cell Signaling Proteinsmentioning
confidence: 77%
See 3 more Smart Citations
“…We next sought to examine the effect of the ΔF233 mutation on the acyltransferase activity of DHHC21. Previously, we detected direct stimulus-dependent interaction between DHHC21 and the Src-family kinase Lck (Fan et al, 2020). Furthermore, we showed that shRNAmediated downregulation of DHHC21 significantly decreased Sacylation of Lck and PLC-γ1 in resting EL4 lymphoma cells, suggesting that these proteins are direct targets of DHHC21 (Fan et al, 2020).…”
Section: Dhhc21 Mediates Tcr-induced S-acylation Of T Cell Signaling Proteinsmentioning
confidence: 77%
“…The transmembrane adaptor LAT has been reported to be dually S-acylated at cysteine residues located proximally to the inner face of the plasma membrane, and a selective defect in LAT S-acylation has been found to be associated with a state of T cell functional unresponsiveness known as T cell anergy (Hundt et al, 2006). Recently, a candidate-based screening of the proximal TCR signaling components allowed us to detect previously uncharacterized S-acylation of adaptor protein GRB2, PLC-γ1 and tyrosine kinase ZAP-70 (Fan et al, 2020;Tewari et al, 2021). A functional analysis of ZAP-70 S-acylation revealed that this modification is essential for ZAP-70 interaction with its protein substrates and subsequent transcriptional responses (Tewari et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Owing to their recent identification, little is known about the role of DHHC PATs in the regulation of the immune responses. Earlier, we identified DHHC21 as a PAT controlling T cell activation and differentiation of naive CD4 + T cells into T helper (Th) Th1 and Th2 subtypes ( 33 ). Downregulation of DHHC21 prevented S-acylation of Lck, Fyn, and LAT, suggesting that this enzyme could be involved in the regulation of proximal TCR signaling.…”
Section: Discussionmentioning
confidence: 99%